Environmental issues and ILCA research agenda - Swallow, B.M. (International Livestock Centre for Africa, 1993)
As the only international centre that is solely concerned with African livestock, ILCA has a responsibility to play a lead role in defining the agenda of research issues related to livestock development and environmental policy in Africa. This paper presents a framework appropriate for defining that agenda and for guiding analysis of particular research issues and gives some detail on how ILCA might approach the specific area of range management policy in the arid and semi-arid areas.